Growth and Seed Quality Responses of Soybean (Glycine max (L.) Merr. var. Chiang Mai 60) in Full Bloom Stage Sprayed with Calcium Chloride under Water Deficit - Banthoengsuk, Saowalak; Boonmachai, Waraluk (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2023)
The objective of this study was to study growth and seed quality responses of soybean var. Chiang Mai 60 at full bloom stage sprayed by calcium chloride (CaCl2) with different concentrations (0, 20, 40 or 60 millimolar (mM)) under water deficit for 7 days in the greenhouse of Chiang Mai Seed Research and Development Center, Nong Han, San Sai, Chiang Mai province. The result showed that spraying CaCl2 under water deficit had no effect on the plant height, number of nodes per plant, number of branches per plant, number of pods per plant, weight per 100 seeds, total seed weight, seed germination rate, hard seed percentage, dead seed percentage, germination index, seed moisture content, protein content, and lipid content. However, the soybean sprayed with 60 mM CaCl2 showed the greatest seed width and length. In addition, the abnormal germination rate was increased when it was not supplemented with CaCl2 (0 mM).